Analysis of the Use of Forecasting to Compare Financing Options and Its Impact on Business Decisions - Singkeruang, A. We Tenri Fatimah; Saeni, Nuraeni; Ramlah, Ramlah; Sari M, Fitri Indah (Advances in Management & Financial Reporting, 2025)
Purpose: This study aims to explore the role of forecasting in comparing financing options and its impact on business decision-making. It focuses on how forecasting tools help companies select financing strategies that align with their long-term financial goals and sustainability objectives. Research Method: A Systematic Literature Review (SLR) methodology was employed to analyze existing studies related to forecasting in financial decision-making, with a particular emphasis on integrating sustainability factors, such as environmental, social, and governance (ESG) considerations, into financing decisions. Results and Discussion: The findings highlight that forecasting gives businesses essential insights into future cash flows, capital needs, and market conditions, enabling informed financing decisions. Accurate forecasting influences the choice between debt and equity financing, mitigates financial risks, and improves long-term stability. The study also highlights the growing importance of incorporating ESG factors into financial forecasting to align financing decisions with sustainability goals. This trend is becoming increasingly relevant in modern corporate finance. Implications: The practical implications suggest businesses integrate forecasting models, including financial and ESG metrics, to ensure sustainable financing decisions. By forecasting, companies can effectively manage risks, enhance adaptability, and align their financial strategies with long-term objectives. This research contributes to the field by offering a novel approach that merges traditional economic analysis with sustainability considerations, providing financial managers with the tools to make data-driven, strategic decisions.